2023
DOI: 10.1186/s13018-023-03540-y
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of upper limb function and postoperative pain in children with lateral humeral condyle fractures were examined retrospectively in relation to the effects of brachial plexus block given in conjunction with general anesthesia

Abstract: Objective To assess in retrospect the effects of brachial plexus block and general anesthesia on children with lateral humeral condyle fractures in terms of postoperative pain and return of upper limb function. Methods Randomly allocated to either the control group (n = 51) or the study group (n = 55) were children with lateral humeral condyle fractures who were admitted to our hospital between October 2020 and October 2021, depending on the surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Finally, this study observed that the addition of BPB on the basis of sevoflurane has good safety and does not increase the occurrence of adverse reactions. This may be due to the fact that BPB directly blocks the nerve of the affected limb in children with humerus fracture, and the depth of anesthesia is controllable, which is helpful to reduce the respiratory and circulatory inhibition caused by excessive dosage of anesthetic drugs, and thus does not increase the occurrence of drowsiness, restlessness, nausea and vomiting in children during postoperative anesthesia recovery (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study observed that the addition of BPB on the basis of sevoflurane has good safety and does not increase the occurrence of adverse reactions. This may be due to the fact that BPB directly blocks the nerve of the affected limb in children with humerus fracture, and the depth of anesthesia is controllable, which is helpful to reduce the respiratory and circulatory inhibition caused by excessive dosage of anesthetic drugs, and thus does not increase the occurrence of drowsiness, restlessness, nausea and vomiting in children during postoperative anesthesia recovery (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%